Memory Performance for Everyday Motivational and Neutral Objects Is Dissociable from Attention - Schomaker, Judith; Wittmann, Bianca C. (Frontiers in Behavioral Neuroscience, 2017)
Episodic memory is typically better for items coupled with monetary reward or punishment during encoding. It is yet unclear whether memory is also enhanced for everyday objects with appetitive or aversive values learned through a lifetime of experience, and to what extent episodic memory enhancement for motivational and neutral items is attributable to attention. In a first experiment, we investigated attention to everyday motivational objects using eye-tracking during free-viewing and subsequently tested episodic memory using a remember/know procedure. Attention was directed more to aversive stimuli, as evidenced by longer viewing durations, whereas recollection was higher for both appetitive and aversive objects. In the second experiment, we manipulated the visual salience of neutral objects through changes of contrast to further dissociate attention and memory encoding. While objects presented with high visual contrast were looked at longer, recollection was best for objects presented in unmodified, medium contrast. Generalized logistic mixed models on recollection performance showed that total viewing duration did not predict subsequent memory, while motivational value (experiment 1) and visual contrast (experiment 2) had quadratic effects in opposite directions. Our findings suggest that an enhancement of incidental memory encoding for appetitive items can occur without an increase in attention and, vice versa, that enhanced attention towards salient neutral objects is not necessarily associated with memory improvement. Together, our results provide evidence for a double dissociation of attention and memory effects under certain conditions.